Emphysematous and xanthogranulomatous pyelonephritis: rare diagnosis - Ramos,Lya Duarte (2010)
Pyelonephritis is a pyogenic infection of renal parenchyma that involves the renal pelvis. It is generally of easy diagnosis. The present case report aims to describe two different manifestations of this infection: xanthogranulomatous pyelonephritis and emphysematous pyelonephritis, which have poor prognosis and require a more effective treatment. The two cases were women in the fiftieth and sixtieth decade of life, with diabetes mellitus and history of weight loss. The diagnosis of the renal infection was established through computed tomography and the treatment was based in surgical procedure, with favorable outcome.